Appalachia : [compact disc] / music from home. - Stanley, Ralph; Scott, Darrell, 1949-; Ritchie, Jean; Williams, Linda; Williams, Robin, 1947-; Boggs, Dock, 1898-1971 (Lonesome Records, 2009)
A richly diverse sampling of music captures the spirit and many cultures of the people who have lived in the Appalachian region.